How Does the Corrected Exhalyzer Software Change the Predictive Value of LCI in Pulmonary Exacerbations in Children with Cystic Fibrosis? - Irena Wojsyk-Banaszak; Zuzanna Stachowiak; Barbara Więckowska; Marta Andrzejewska; Katarzyna Tąpolska-Jóźwiak; Aleksandra Szczepankiewicz; Paulina Sobkowiak; Anna Bręborowicz (Diagnostics, 2023)
Aim: Recently, the most commonly used for multiple breath washout device, the Exhalyzer D, has been shown to overestimate lung clearance index (LCI) results due to a software error. Our study aimed to compare the predictive values of LCI in the CF pulmonary exacerbations (PE) calculated with the updated (3.3.1) and the previous (3.2.1) version of the Spiroware software. Materials and Methods: The measurements were performed during 259 visits in CF pediatric patients. We used 39ΔPE pairs (PE preceded by stable visit) and 138ΔS pairs (stable visit preceded by stable visit) to compare the LCI changes during PE. The areas under the receiver operating curves (AUCROC) and odds ratios were calculated based on the differences between ΔPEs and ΔSs. The exacerbation risk was estimated using a logistic regression model with generalized estimating equations (GEE). Results: There were statistically significant differences in LCI 2.5% median values measured using the two versions of the software in the stable condition but not during PE. The AUCROC for changes between the two consecutive visits for LCI did not change significantly using the updated Spiroware software. Conclusions: Despite the lower median values, using the recalculated LCI values does not influence the diagnostic accuracy of this parameter in CF PE.